Incidence of Naira Redesign on Households Real Income and Consumption Behaviour in Abeokuta South Local Government, Ogun State Nigeria (Lapai Journal of Economics, 2024)
The research examined effects of Naira redesign on households’ real income and consumption behaviour in Abeokuta South LGA, Ogun State. Structured questionnaires were used to collect data. Cluster sampling technique was used to divide households in the study area into blocs/clusters given their similarities in socioeconomic lifestyle with little or no peculiarities. A sample size of 226 households was drawn. Research results showed that the policy has a negative effect on both real income and consumption behaviour of households in Abeokuta South LGA. The study recommends that government should embark on phasing out old Naira notes on a gradual basis, while ensuring that the released newly minted notes matches the quantity of mopped out old currency. The CBN should ensure that adequate information is disseminated, while giving ample time to adjust to the new development so as to avert unwarranted hardship.